Social drivers of colony collapse disorder in Benin’s beekeeping, West Africa - FELICIEN AMAKPE; BRICE SINSIN (Asian Journal of Agriculture, 2025)
Abstract. Amakpe F, Sinsin B. 2025. Social drivers of colony collapse disorder in Benin’s beekeeping, West Africa. Asian J Agric 9: 391-401. The colony collapse disorder is a worldwide factor of the honeybee population decline. In the tropical African regions, recurrent bushfires, uncontrolled agricultural pesticide, unproper beekeeping system, pests, and diseases are contributing factors that worsen the colony collapse disorder in contrary to western beekeeping, where the phenomenon is better controlled. In addition to these environmental and managerial drivers, the beekeeping potential in Benin is handicapped by the countrywide massive destruction of honeybee colonies by unknown individuals. We assessed the impacts of this phenomenon, termed in this study the social colony collapse disorder, through surveys and group discussions on 96 apiaries, distributed in the entire country from January 2023 to January 2024. The investigations targeted apiaries bearing at least five honeybee colonies, and the respondents were the apiary owners. 31.4% of the country's honeybee colonies and 72.9% of apiaries were impacted. 7.3±7.1 colonies were lost per apiary from January 2023 to January 2024.  99% of the impacts occurred during the honey season (October to May), and the honeybee colony thieves mainly operated at night. The departments of Zou (78.4% of its colonies), Collines (60.3%), and Donga (40.8%) were the most impacted, and experimental apiaries were not spared. It is a neglected key factor that discourages beekeepers and hinders beekeeping mainstreaming for poverty alleviation in Benin, where no operational mitigation approach is effective to date. Reinforcing the local mitigation attempts and improving the beekeeping legal framework will help reduce the attacks. This will require deeper investigations for elaborating the case-by-case eradication approaches per beekeeping region in Benin and for elaborating a regional synergetic mitigation action plan in the entire West Africa.